Renewable indoor radiant cooling and earth tube heat exchanger hybrid for thermal comfort improvement - M.S. Imran,; A. Baharun,; S.H. Ibrahim,; W.A.W.Z. Abidin, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study investigates the applicability of hydronic radiant cooling system charged with night cooled water to cool down building in Sarawak particularly for low income building to a thermally acceptable level. The system uses night sky as well as the ground as a heat sink source to passively cool the building while operating at a low energy level. Results from building energy simulation program or Energy Plus shows that for a stand-alone hydronic radiant system only 77% of the time the thermal condition could meet ASHRAE acceptable PMV thermal condition between -0.5 and + 0.5. Another simulation of the radiant and earth tube system hybrid further improved the indoor thermal condition significantly by 100% to meet the same PMV level. The hybrid system was able to improve the baseline uncomfortable operative temperature of 37oC to 28.5oC while meeting the average comfort zone upper limit for Malaysia of 30.1 oC. Simulation on energy spent shows that as much as 94% energy could be saved by using the hybrid system. This level of saving is not impossible as renewable night cooled water was used to charge the indoor hydronic radiant cooling system.